Answer:
x=0, - 9
Step-by-step explanation:
x^2+9x=0
x(x+9)=0
x=0 or x=-9
Answer:
C
Step-by-step explanation:
The original is L, if it was roated 180 degrees clockwise it would be in the same spot
Answer:
39
Step-by-step explanation:
![f(x) = 2x - 1.....(1) \\ g(x) = 3x + 5....(2) \\ plug \: x = 5 \: in \: (2) \\ g(5) = 3 \times 5 + 5 = 15 + 5 = 20 \\ \therefore \: f(g(5)) = 2 \times 20 - 1 = 40 - 1 = 39 \\ \\ \huge \red{ \boxed{\therefore \: f(g(5)) =39}}](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%20-%201.....%281%29%20%5C%5C%20g%28x%29%20%3D%203x%20%2B%205....%282%29%20%5C%5C%20plug%20%5C%3A%20x%20%3D%205%20%5C%3A%20in%20%5C%3A%20%282%29%20%5C%5C%20g%285%29%20%3D%203%20%5Ctimes%205%20%2B%205%20%3D%2015%20%2B%205%20%3D%2020%20%5C%5C%20%20%5Ctherefore%20%5C%3A%20f%28g%285%29%29%20%3D%202%20%5Ctimes%2020%20-%201%20%3D%2040%20-%201%20%3D%2039%20%5C%5C%20%20%5C%5C%20%20%20%5Chuge%20%5Cred%7B%20%5Cboxed%7B%5Ctherefore%20%5C%3A%20f%28g%285%29%29%20%3D39%7D%7D)
If you mean to the nearest HUNDREDTH the answer is 14.60.
Step-by-step explanation:
Given the expression,
, we want to know which sign placed in between the two polynomial will produce a binomial.
Using a plus (+) sign to check:
![= (3y ^ 6 + 4) + (9y ^ {12} - 12y ^ 6 + 16)\\= (3y ^ 6 + 4) + (9y ^ {12} - 12y ^ 6 + 16)\\collect \ like \ terms\\= 9y^{12} +3y^6 - 12y^6 + 16+ 4\\= 9y^{12} - 9y^6 + 20\\](https://tex.z-dn.net/?f=%3D%20%283y%20%5E%206%20%2B%204%29%20%2B%20%289y%20%5E%20%7B12%7D%20-%2012y%20%5E%206%20%2B%2016%29%5C%5C%3D%20%20%283y%20%5E%206%20%2B%204%29%20%2B%20%289y%20%5E%20%7B12%7D%20-%2012y%20%5E%206%20%2B%2016%29%5C%5Ccollect%20%5C%20like%20%5C%20terms%5C%5C%3D%209y%5E%7B12%7D%20%2B3y%5E6%20-%2012y%5E6%20%2B%2016%2B%204%5C%5C%3D%209y%5E%7B12%7D%20-%209y%5E6%20%2B%2020%5C%5C)
From the gotten value, it can be seen that the resulting answer produces 3 terms, showing that it results in a trinomial instead of binomial.
Using a plus (-) sign to check:
![= (3y ^ 6 + 4) - (9y ^ {12} - 12y ^ 6 + 16)\\= 3y ^ 6 + 4 - 9y ^ {12} + 12y ^ 6 - 16\\collect \ like \ terms\\= -9y^{12} +3y^6 +12y^6 + 4-16\\= -9y^{12} +15y^6 -12\\](https://tex.z-dn.net/?f=%3D%20%283y%20%5E%206%20%2B%204%29%20-%20%289y%20%5E%20%7B12%7D%20-%2012y%20%5E%206%20%2B%2016%29%5C%5C%3D%20%203y%20%5E%206%20%2B%204%20-%209y%20%5E%20%7B12%7D%20%2B%2012y%20%5E%206%20-%2016%5C%5Ccollect%20%5C%20like%20%5C%20terms%5C%5C%3D%20-9y%5E%7B12%7D%20%2B3y%5E6%20%2B12y%5E6%20%2B%204-16%5C%5C%3D%20-9y%5E%7B12%7D%20%2B15y%5E6%20-12%5C%5C)
From the gotten value, it can be seen that the resulting answer produces 3 terms, showing that it results in a trinomial instead of binomial.
<em>Hence none of the operations given results in a binomial</em>